Electronic structure of confined carbyne from joint wavelength-dependent resonant Raman spectroscopy and density functional theory investigations. (15th April 2022) - Martinati, Miles; Wenseleers, Wim; Shi, Lei; Pratik, Saied Md; Rohringer, Philip; Cui, Weili; Pichler, Thomas; Coropceanu, Veaceslav; Brédas, Jean-Luc; Cambré, Sofie
Abstract: Carbyne, i.e. an infinitely long linear carbon chain (LCC), has been at the focus of a lot of research for quite a while, yet its optical, electronic, and vibrational properties have only recently started to become accessible experimentally thanks to its synthesis inside carbon nanotubes (CNTs). While the role of the host CNT in determining the optical gap of the LCCs has been studied previously, little is known about the excited states of such ultralong LCCs. In this work, we employ the selectivity of wavelength-dependent resonant Raman spectroscopy to investigate the excited states of ultralong LCCs encapsulated inside double-walled CNTs. In addition to the optical gap, the Raman resonance profile shows three additional resonances. Corroborated with DFT calculations on LCCs with up to 100 carbon atoms, we assign these resonances to a vibronic series of a different electronic state. Indeed, the calculations predict the existence of two optically allowed electronic states separated by an energy of 0.14–0.22 eV in the limit of an infinite chain, in agreement with the experimental results. Furthermore, among these two states, the one with highest energy is also characterized by the largest electron-vibration couplings, which explains the corresponding vibronic series of overtones. Graphical abstract: Image 1